Além dos jogos escolares: possibilidades de eventos para a Educação Física como componente curricular - Novaes, Allan Jhones da Silva (2023)
This is a qualitative research based on the assumptions of action research. We investigate a pedagogical proposal in which we consider the culminating events as part of the teaching-learning process. These culminations, in turn, were organized following guiding principles conceived from the collective construction between three Physical Education teachers who work in the same school unit in the city of Quissamã-RJ. Thus, the objective of the research is to investigate a pedagogical proposal based on didactic sequences that incorporate culminating events into the Physical Education curriculum. The research was divided into two stages: in the first stage, 3 teachers participated, including the author of this thesis who organized themselves to discuss the objectives of school Physical Education and the only event themed by the curricular component in the research network; and in the second stage, two didactic sequences were developed, following the annual planning of the teachers, which culminated in events related to the content of each bimester in which the interventions were applied. We conclude that the organization of events in line with the Physical Education curricular component is a feasible possibility, presenting itself as a strategy for student adherence to classes, as well as providing a path for the construction of autonomy, creativity and protagonism and strengthening of Physical Education as a curricular component of Basic Education.